High-performance solution-processed Ti3C2Tx MXene doped ZnSnO thin-film transistors via the formation of a two-dimensional electron gas. Issue 32 (5th August 2021) - Zhao, Tianshi; Liu, Chenguang; Zhao, Chun; Xu, Wangying; Liu, Yina; Mitrovic, Ivona Z.; Lim, Eng Gee; Yang, Li; Zhao, Ce Zhou
Abstract : The optimization of solution-processed ZTO TFTs was successfully realized by fabricating a channel layer into a homojunction structure (MXene doped ZTO/ZTO) to form a 2DEG. The device shows excellent electrical performance with a maximum annealing temperature of ≤300 °C. Abstract : MXenes are a large class of two-dimensional (2D) materials widely studied recently since they have good water solubility and are able to tune the work function (WF) of materials without changing their electronic characteristics. Based on this, aqueous solution-processed indium-free zinc tin oxide (ZTO) thin-film transistors (TFTs) have been fabricated under an annealing temperature of 300 °C and successfully optimized. This optimization is achieved by fabricating a channel layer into a homojunction structure (MXene doped ZTO/ZTO) to form a two-dimensional electron gas (2DEG). Through doping the specific concentrations of Ti3 C2 T x MXenes into the upper layer ZTO thin films, the TFTs exhibit enhanced field-effect mobilities ( μ FE ) of 10.77 cm 2 V −1 s −1 and 13.06 cm 2 V −1 s −1 as well as a large on/off current ratio of more than 10 8 . Moreover, compared with the undoped double-layer ZTO TFTs, the homojunction devices show better stability, mainly resulting from the transformation in leading conduction mode. Finally, through applying the homojunction channel on the solution-processed aluminum oxide (AlO x ) dielectric layer, the μ FE exhibits a further enhanced value of 28.35 cm 2 V −1 s −1 . This is the first report to apply MXenes to the channel layer of TFTs and to fabricate solution-processed ZTO thin films via an aqueous solvent under 300 °C.